Exploring Students’ Perceptions of Speaking Practice with Procedural Texts to Improve English Fluency - Dwi Ayu Lestari; Yeni Rahmawati; Rani Herning Puspita (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
English speaking skills are fundamental for success in the global era, yet many students face significant challenges in developing these abilities, particularly due to anxiety, limited vocabulary, and uninspiring instructional methods. This study explores students’ perceptions of using procedural texts as a strategy to improve their English-speaking fluency. Procedural texts, which provide structured and systematic language patterns, are believed to enhance students’ ability to articulate ideas coherently while reducing speaking anxiety. Employing a qualitative descriptive approach, data will be collected through semi-structured interviews and classroom observations involving six vocational high school students majoring in automotive engineering, who have been selected by gathering students with the highest and lowest English scores from each class. From each of the three classes, two students are chosen, one with the highest and one with the lowest score, resulting in six participants. Each of the Thematic analyses was used to identify recurring patterns in students' experiences and viewpoints. This study holds significance as it provides empirical insights into alternative pedagogical approaches aimed at addressing common challenges to speaking proficiency among vocational students, an often-underrepresented population in second language acquisition research. The implications of the study suggest that integrating procedural texts into English instruction can effectively improve speaking fluency and reduce anxiety, particularly for students in vocational settings. However, the study's limitations, including the small sample size and its focus on a specific group of students from a single vocational field, suggest the need for further research with larger and more diverse samples to explore the broader applicability and long-term effects of procedural text-based instruction.